CONDIÇÕES PRELIMINARES PARA A GERMINAÇÃO DE SEMENTES DE CANDIÚBA (Trema micrantha (L.) Blume.)1 - Castellani, Estela Dalpim; Aguiar, Ivor Bergemann De [UNESP] (Departamento de Engenharia Agrícola - UFCG, 1998)
Trema micrantha (Ulmaceae) is a common pioneer tree species in Brazil, much used in the São Paulo State for recovery of degraded areas. Preliminary conditions to favour the seed germination of T. micrantha were studied in this work. The fruits were harvested in Jaboticabal (SP) and separated into two maturation stages: of green colour and of green/red or red colours. The germination tests were carried out with fruits (fruits with pulp) and seeds (fruits without pulp), on sand and filter paper substrates, and under constant (25°C) and alternate (20-30°C) temperatures. An eight-hour photoperiod was used and the final percentage and the speed germination of the seeds were evaluated. It was found that the seeds didn't germinate at 25°C and the results obtained at 20-30°C showed that (a) seed germination wasn't affected by the tested substrates; (b) pulp removal favoured the seed germination; and (c) better physiological quality was obtained with seeds from green/red and red fruits.

Trema micrantha (candiúba) - Ulmaceae - é uma espécie arbórea pioneira de ampla ocorrência natural no Brasil e muito utilizada no Estado de São Paulo para a recuperação ambiental de áreas degradadas. Este experimento teve por objetivo definir, preliminarmente, algumas condições que favorecem a germinação das sementes de candiúba. Os frutos foram colhidos no Campus da UNESP, em Jaboticabal, SP, e separados em dois estádios de maturação: de coloração verde e de coloração avermelhada (verde-vermelho e vermelha). Os testes de germinação foram conduzidos com frutos (sem despolpamento) e com sementes (frutos despolpados) em dois substratos (sobre areia e sobre papel de filtro) nas temperaturas constante de 25°C e alternada de 20-30°C. O fotoperíodo adotado foi de oito horas, tendo sido avaliadas a porcentagem final e a velocidade de germinação das sementes. As sementes não germinaram a 25°C e os resultados obtidos a 20-30°C mostraram que: (a) o comportamento germinativo das sementes foi o mesmo nos dois substratos testados; (b) o despolpamento favoreceu a germinação das sementes; e (c) a qualidade fisiológica das sementes provenientes de frutos avermelhados foi superior à das provenientes de frutos de coloração verde.
PRELIMINARY CONDITIONS FOR GERMINATION OF Trema micrantha (L.) Blume. SEEDS
Keywords: forest seed; maturation; pulp removal; substrate; temperature; semente florestal; maturação; despolpamento; substrato; temperatura